SYNTHESIS AND CHARACTERIZATION OF ALPHA TERPINEOL FROM TURPENTINE-DERIVED PINUS MERKUSII WASTE USING p-TOLUENE SULFONIC ACID CATALYST - Berghuis, Nila Tanyela; Sari, Nurul Puspita (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Pine tree sap can be distilled to produce gondorukem and turpentine with alpha-pinene as the primary compound (65-85%). The alpha-pinene contained in turpentine can be reacted with alcohol to produce alpha terpineol which has a higher selling value. The study aimed was to synthesize alpha terpineol from turpentine derived from processing pine tree sap with varying percentages of p- toluenesulfonic acid (p-TSA) catalyst (5, 10, 15%), reaction time (2, 4, 6 hours), and by comparing extracted and commercial turpentine as starting materials. The alpha-terpineol yields for a 10% catalyst were 53,515%; 54.28%; 62.08% and 15% catalyst amounting to 89.24%; 89.68%; 91.95%, as well as 15% catalyst with turpentine extraction of 92.96%. The densities for 10% alpha terpineol catalyst were 0.969 g/mL, 0.971 g/mL, and 0.969g/mL and with 15% catalyst were 0.969 g/mL, 0.972 g/mL, and 0.971 g/mL. The results of FTIR analysis for alpha terpineol samples with 10 and 15% catalyst for 2, 4 and 6 hours showed the presence of O-H and C-O functional groups. GC-MS analysis for alpha terpineol levels was obtained at 25.88% (10% catalyst) and 24.52% (15% catalyst). Several component compounds were obtained, namely 1-Cyclopentene-1-methanol, alpha, 4,5-tetramethyl-, trans.